2013
DOI: 10.4081/jlimnol.2013.e18
|View full text |Cite
|
Sign up to set email alerts
|

Hatching phenology and voltinism of Heterocypris barbara (Crustacea: Ostracoda) from Lampedusa (Sicily, Italy)

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 64 publications
(75 reference statements)
2
24
0
Order By: Relevance
“…It is known that water temperature and conductivity are important factors controlling the development rate of aquatic crustaceans (Roca and Wansard 1997;Aguilar-Alberola and Mesquita-Joanes 2011;Rossi et al 2013). In fact, the estimated development time of C. pubera was clearly dependent on these parameters, being shorter towards the summer, when temperature and conductivity increased.…”
Section: Journal Of Natural History 1039mentioning
confidence: 97%
See 2 more Smart Citations
“…It is known that water temperature and conductivity are important factors controlling the development rate of aquatic crustaceans (Roca and Wansard 1997;Aguilar-Alberola and Mesquita-Joanes 2011;Rossi et al 2013). In fact, the estimated development time of C. pubera was clearly dependent on these parameters, being shorter towards the summer, when temperature and conductivity increased.…”
Section: Journal Of Natural History 1039mentioning
confidence: 97%
“…Heterocypris salina (Brady 1868), another Cyprididae inhabitant of shallow ponds, is able to produce two or three generations per year depending on water temperature (Ganning 1971). Additionally, several studies have shown that other crustaceans, like copepods, can alternate between univoltine and multivoltine strategies according to relevant environmental variables, such as temperature, food availability, photoperiod and hydroperiod (Rossi et al 2013).…”
Section: Journal Of Natural History 1039mentioning
confidence: 99%
See 1 more Smart Citation
“…Species of the genus Heterocypris have been recorded in different places with very different environmental conditions (mezquita et al, 1999;Petkowski et al, 2000;Rossi et al, 2013), and H. incongruens can be considered as cosmopolitan or a widely distributed species (mezquita et al, 1999). they are able to sustain dense populations in places with several stressors acting upon them simultaneously, as in eutrophic or temporary water bodies.…”
Section: Discussionmentioning
confidence: 99%
“…they are highly tolerant because they inhabit different types of environments, from hot springs to lakes in the arctic (delorme, 1991;Külköylüoğlu et al, 2007). Some studies on ostracods have examined different features that allow them to remain in aquatic systems, for example, Rossi et al (2013) and Vandekerkhove et al (2013) show that Heterocypris incongruens and Eucypris virens exhibit a high viability in egg resistance to different stresses such as hypoxia, insecticides, digestive enzymes, high salinity, and UV radiation. Horne (1993) and aguilar-alberola and mesquita-Joanes (2011) also show that juvenile and adult Candona patzcuaro and Heterocypris bosniaca can live in dry soil for up to 5 weeks.…”
Section: Introductionmentioning
confidence: 99%